Embolisation of pancreatic pseudoaneurysm in pregnancy: a rare case report - Jayakumar, Aarthy; Janakiraman, Prabha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Pancreatic pseudoaneurysm is a rare and life threatening complication in pregnancy. It is a vascular complication of pancreatitis which may lead to erosion of pancreatic artery into a pseudocyst. Pseudocysts accounts for 5% in pancreatitis. Herewith we are presenting a case of pancreatic pseudoaneurysm in pregnancy which was successfully managed by placing endovascular placing of coil and obliteration of the same.